GIS for Coastal Zone Management - Bartlett, Darius (CRC Press, 2009)
Increasingly used to analyze and manage marine and coastal zones, Geographical Information Systems (GIS) provide a powerful set of tools for integrating and processing spatial information. These technologies are increasingly used in the management and analysis of the coastal zone. Supplying the guidance necessary to use these tools, GIS for Coastal Zone Management explores key technical, theoretical, and applications issues. Drawing on the practical experience of experts in the field, the book discusses recent developments and specific applications.